Targeting CPT1B as a potential therapeutic strategy in castration‐resistant and enzalutamide‐resistant prostate cancer. Issue 12 (10th July 2020) - Abudurexiti, Mierxiati; Zhu, Wenkai; Wang, Yuchen; Wang, Jun; Xu, Wenhao; Huang, Yongqiang; Zhu, Yao; Shi, Guohai; Zhang, Hailiang; Zhu, Yiping; Shen, Yijun; Dai, Bo; et al.
Abstract: Background: Prostate cancer is characterized by aberrant lipid metabolism, including elevated fatty acid oxidation. Carnitine palmitoyltransferase 1B (CPT1B) catalyzes the rate‐limiting step of fatty acid oxidation. This study aimed to determine if CPT1B has a critical role in prostate cancer progression and to identify its regulatory mechanism. Methods: CPT1B expression data from The Cancer Genome Atlas and Gene Expression Omnibus databases was compared with patient survival data. A tissue microarray was constructed with 60 samples of prostate cancer and immunohistochemically stained for CPT1B. Castration‐resistant prostate cancer (CRPC) cell lines 22RV1 and C4‐2 in which CPT1B expression had been stably knocked down were established; and cell proliferation, cell cycle distribution, and invasion were investigated by Cell Counting Kit‐8 (CCK‐8) and colony formation assays, flow cytometry, and Transwell assays, respectively. To examine the impact of androgen receptor (AR) inhibition on CPT1B expression, JASPAR CORE was searched to identify AR‐binding sites in CPT1B. Dual luciferase and ChIP assays were performed to confirm CPT1B activity and AR binding, respectively. Differentially expressed genes (DEGs) in prostate cancer underwent gene set enrichment analysis (GSEA). Enzalutamide‐resistant C4‐2 cells were generated and the mechanism of enzalutamide resistance and downstream signaling pathway changes of CPT1B to C4‐2 was explored through CCK‐8 test. Results: CPT1B expression was upregulated in human prostate cancer compared with normal prostate tissue and was associated with poor disease‐free survival and overall survival. Silencing of CPT1B resulted in downregulated cell proliferation, reduced S‐phase distribution, and lower invasive ability, whereas the opposite was observed in CRPC cells overexpressing CPTB1. DEGS in prostate cancer were correlated with G‐protein–coupled receptor signaling, molecular transducer activity, and calcium ion binding. AR may regulate CPT1B expression and activity via specific binding sites, as confirmed by dual luciferase and ChIP assays. The CCK‐8 experiment demonstrated that CPT1B overexpression in C4‐2 cells did not significantly increase the ability of enzalutamide resistance. However, overexpression of CPT1B in C4‐2R cells significantly increased the enzalutamide resistance. Upregulation of CPT1B expression increased AKT expression and phosphorylation. Conclusions: CPT1B is upregulated in prostate cancer and is correlated with poor prognosis, indicating its potential as a biomarker. AR inhibits the transcription of CPT1B. In the CRPC cell line, overexpression of CPT1B alone cannot promote enzalutamide resistance, but in the drug‐resistant line C4‐2R, overexpression of CPT1B can promote the resistance of C4‐2R to enzalutamide.